ASPECTS OF SECULARISM AND THE CONSTITUTION OF INDIA - Ahmad Shairgojri, Aadil; Subramanian, Dr. C. (Universitas Efarina, 2022)
Promoting democracy through safeguarding national cohesion and sovereignty is an example of how the secularist principle can be put into practise. The Constitution also includes provisions for the establishment of secular societies. No person shall be subjected to Section 15's discrimination on the basis of his or her religion, race, caste, gender, or country of origin. The right to religious freedom is guaranteed by Article 25. In India, everyone has the freedom to follow whatever faith they choose and to help spread that faith to others. However, religious intolerance has no place in a democratic society. No publicly funded school is required to offer religious instruction in accordance with Section 28. Article 30 guarantees the right of all minorities to found schools that meet their specific needs on the basis of their religion and language.